Predicting financial distress companies in the manufacturing and non-manufacturing sectors in Malaysia using macroeconomic variables - Mohd Norfian Alifiah (Management Science Letters, 2018)
This paper attempts to predict financial distress companies in the manufacturing and non-manufacturing sectors in Malaysia using financial distress companies as the dependent variable and financial ratios and macroeconomic variables as the independent variables. Logit Analysis was used as the analysis procedure because ratios do not have to be normal if it is used. It is also suitable when the dependent variable is binary in nature. Furthermore, it can also provide the probability of a company being financially distressed. This study found that the independent variables that can be used to predict financial distress companies in the manufacturing sector in Malaysia were total assets turnover ratio, current ratio, net income to total assets ratio and money supply (M2). However, the independent variables that can be used to predict financial distress companies in the non-manufacturing sector in Malaysia were debt ratio, working capital ratio, net income to total assets ratio and money supply (M2). This study provides the prediction models of financial distress com-panies in the manufacturing and non-manufacturing sectors in Malaysia using financial ratios and macroeconomic variables as its independent variables.